Assessing Compensation Values from Resettlement Projects: The Need to Incorporate Elements of Freedom and Justice (Global Business Management Review (GBMR), 2022)
The compensation for communities who are relocated to make way for development projects is often underestimated. As a consequence, the displaced communities often find their welfare to be worse off after resettlement and hence, the compensations do not provide justice to them. This paper reviews the issue of compensation and the approach for making compensation. In particular, it reviews the classical compensation theory by Kaldor-Hicks and also the modern theories of compensation. This paper argues that the Kaldor-Hicks compensation criteria are limited to explain the changes in the welfare of the displaced communities after resettlement. Thus, there is a need to consider the elements in Amartya Sen’s conception of freedom, capability and liberty as well as Rawlsian theory of justice in modern compensation theories in order to capture the real changes in the welfare. A broader conceptual framework for the economics of compensation employing the role of freedom is constructed to provide a comprehensive understanding on the role of freedom and rights in compensation valuation for future development projects.